Exogenous 6-Benzyladenine Improves Waterlogging Tolerance in Maize Seedlings by Mitigating Oxidative Stress and Upregulating the Ascorbate-Glutathione Cycle - Wang, Ji; Wang, Daye; Zhu, Min; Li, Fenghai (Frontiers in Plant Science, 2021)
6-benzyladenine (6-BA) is a synthetic plant growth regulator belonging to cytokinin category that can overcome the negative effects of various abiotic stresses including waterlogging in crop plants. This study aimed to investigate the effects of exogenous 6-BA on growth, oxidative stress and Ascorbate-Glutathione (AsA-GSH) cycle system in waxy corn inbred seedlings SY-MY13 (waterlogging resistant) and SY-XT1 (waterlogging sensitive) under waterlogging stress. Waterlogging induces the accumulation of intracellular reactive oxygen species (ROS), increases the contents of O2·−, H2O2, malondialdehyde (MDA) and the value of relative electric conductivity (REC%), which in turn causes apoptosis, obstructs plants growth and development. SY-MY13 exhibited better growth than SY-XT1 under waterlogging, this was due to SY-MY13 possessed excellent waterlogging resistance. However, the application of exogenous 6-BA could not only reduce the accumulation of ROS and increase the activities of ascorbate peroxidase (APX), glutathione reductase (GR), dehydroascorbate reductase (DHAR) and monodehydroascorbate reductase (MDHAR) and enhance the contents of ascorbic acid (AsA) and reduced glutathione (GSH), regulate efficiency of AsA-GSH cycle system but also promote the growth and development of seedlings. Hence, In addition to this, the application of exogenous 6-BA can alleviate the waterlogging induced damages and improve waterlogging tolerance in waxy corn through the activation of AsA-GSH cycle system and the elimination of ROS.